Improvement of electrical and energy harvesting properties of new lead-free BST modified 0.995BNKT–0.005LN ceramics - Pimpilai Wannasut; Panupong Jaiban; Pharatree Jaita; Methee Promsawat; Orawan Khamman; Anucha Watcharapasorn (Journal of Asian Ceramic Societies, 2023)
ABSTRACTNew lead-free (1-y)[0.995Bi0.5(Na0.80K0.20)0.5TiO3-0.005LiNbO3]-y[(Ba0.7Sr0.3)TiO3] or (1-y)[0.995BNKT-0.005LN]-y[BST] (where y = 0, 0.01, 0.02, 0.03, 0.04 and 0.05 mol fraction) ceramics were fabricated by a conventional sintering method with two calcination steps. All ceramics sintered at 1125°C for 2 hours showed an optimum relative density of ~98% and a linear shrinkage of ~18%. X-ray diffraction patterns indicated that all ceramics possessed a pure perovskite phase with coexisting rhombohedral and tetragonal structures. Electrical and energy harvesting properties of 0.995BNKT–0.005LN ceramics were improved with 0.03 mol fraction BST addition (d33 = 287 pC/N, d*33  = 440 pm/V, g33 = 13.40 × 10−3 V/mN and FoM = 3.85 pm2/N). From the observed results, the 0.97[0.995BNKT-0.005LN]-0.03[BST] ceramic is a promising candidate for lead-free piezoelelectric sensor-actuator and energy harvester.